2013
DOI: 10.1002/ange.201302524
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cooperative Binding of Ion‐Pair Dimers and Ion Quartets by a Bis(calix[4]pyrrole) Macrotricyclic Receptor

Abstract: Vier verbindet: Ein makrotricyclischer Rezeptor mit zwei konvergenten Calix[4]pyrrol‐Einheiten zeichnet sich durch die ungewöhnliche Bindung zweier Ionenpaare aus. Im Fall von Tetrabutylammonium(TBA)‐Salzen werden die Paare hoch kooperativ gebunden. MTOA=Methyltrioctylammonium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In recent work by Valderrey et al, 42 a bis(calix [4]pyrrole) receptor 90 ( Figure 28) was shown to form an unprecedented five-component complex by the combination of cascade contact ion-pair binding modes. The addition of 2 equiv of tetrabutylammonium cyanate (TBA + NCO À ) resulted in the formation of a cascade complex with two NCO À anions bound to the calix [4]pyrrole anion-binding sites and one TBA + cation sandwiched between forming contact ion-pair interactions.…”
Section: Ion-pair Bindingmentioning
confidence: 98%
“…In recent work by Valderrey et al, 42 a bis(calix [4]pyrrole) receptor 90 ( Figure 28) was shown to form an unprecedented five-component complex by the combination of cascade contact ion-pair binding modes. The addition of 2 equiv of tetrabutylammonium cyanate (TBA + NCO À ) resulted in the formation of a cascade complex with two NCO À anions bound to the calix [4]pyrrole anion-binding sites and one TBA + cation sandwiched between forming contact ion-pair interactions.…”
Section: Ion-pair Bindingmentioning
confidence: 98%